The effect of different type of plasticizers on gelatin-sago starch composite edible film for food packaging: article - Alias, Nurul Atiqah; Hamidon, Fariza (2019)
The objective of this study is to produce gelatinsago starch composite edible film plasticized with glycerol and polyethylene glycol (PEG) 200, to conduct the physical and mechanical test of the glycerol and PEG 200 plasticized films, and also to determine the suitable types of plasticizers (glycerol and PEG 200) to be used in food packaging. The effectiveness of this edible film was evaluated by conducting the thickness, tensile strength and elongation at break, water vapor permeability, water solubility, FTIR, and also thermogravimetric analyses. Films were prepared by plasticizers concentration of 40%, 50%, 60% and 70% w/w of solution. Films plasticized with glycerol were thicker than films with PEG 200. This was due to the gelatin higher protein content which led to a higher viscosity and greater thickness. Glycerol plasticized films had a higher solubility compared to PEG 200 plasticized films due to the glycerol massive interaction with the gelatin-starch molecule. For the Tensile strength (TS), from the result it can be seen that the TS of GS starch film decreases with increasing plasticizers concentration from 40% to 70% and films with glycerol showed higher TS than films with PEG 200. The WVP analysis showed that the PEG 200 exhibit higher WVP than glycerol thus shows that glycerol was the best plasticizers to be used as food packaging as it had a low WVP. Meanwhile, from FTIR analysis, the absorption bands belong to the OH and CH vibrations. The thermal stability analysis showed that the glycerol TGA curves had a greater degradation rate compared to PEG 200. So the film stability in film plasticized with glycerol was higher than in PEG 200 plasticized film. But generally it indicates that the films were still stable at temperature below 100°C and still can be used for many food packaging applications. Through the conducted analysis, it can be concluded that the glycerol is the better plasticizer to be used in food packaging applications compared to PEG 200.